The role of village institutions and the welfare of tobacco farmers in Ganti Village, Central Lombok - Nur Adhi, Rakhmat; Sumitro,; Utomo, Jepri; Febriani, Haniza (Tamalanrea: Journal of Government and Development (JGD), 2025)
This study examines the role of village institutions in improving the welfare of tobacco farmers in Ganti Village, Central Lombok. Tobacco is a strategic commodity that supports the rural economy, but it still faces structural inequalities in distribution, market access, and the dominance of middlemen.Using a qualitative approach, this study describes the dynamics of village institutions such as farmer groups, village-owned enterprises (BUMDes), and the role of customary institutions in intervening in the local economy. The findings indicate that village institutions have the potential to act as facilitators, protectors, and liaisons between farmers, markets, and the government. However, institutional challenges such as weak capacity, conflicts of interest, and structural oligarchization also remain obstacles. Therefore, strengthening village institutions in a democratic and participatory manner is key to creating a just, transparent, and sustainable agrarian system. This study concludes that adaptive local institutional-based development is a crucial foundation for the economic independence of tobacco farmers in Central Lombok.